ChemInform Abstract: A Novel Europium (III) Nitridoborate Eu3[B3N6]: Synthesis, Crystal Structure, Magnetic Properties, and Raman Spectra. Issue 31 (14th July 2016) - Aydemir, Umut; Kokal, Ilkin; Prots, Yurii; Foerster, Tobias; Sichelschmidt, Joerg; Schappacher, Falko M.; Poettgen, Rainer; Ormeci, Alim; Somer, Mehmet
Abstract: The title compound is prepared from a 1:1 molar mixture of Eu3 (BN2 )2 and Br2 (1073 K, 12 h) and characterized by powder and single crystal XRD, ESR, Raman and Moessbauer spectroscopy, and DFT quantum chemical calculations.